The Impact of Using Weight Training on Improving Physical Fitness and Performance among Footballers - Abu-Shihab , Esam Najeh (Dirasat: Educational Sciences, 2021)
This study aims at identifying the impact of using weight training on improving physical fitness elements and the level of skilled performance among footballers. The study sample consisted of (30) footballers from Milton Soccer Academy, less than seventeen years old. The researcher used an experimental approach, where the sample was divided into two identical groups (experimental group and control group), with fifteen footballers in each group, using pre- and post-measurements for nine weeks. The results showed that there are statistically significant differences at (α≤0.05) between the pre- and post-measurements due to the impact of using weight training on improving some physical fitness elements and the level of skilled performance among footballers in favor of the post-measurement. The results also showed that there are statistically significant differences at (α≤0.05) in the post-measurement between the individuals of the experimental and control groups in terms of improving some physical fitness elements and the level of skilled performance among footballers in favor of the experimental group. The research highlights the need for training programs using weights as a method for promoting physical fitness and the level of skilled performance among various age categories and for both males and females.